Study on the Water-Saving Irrigation Technology in the Slope Vegetation Restoration of the Mining Area Dump - Yanping Liu; Jingli He; Zhanqi Liang (The Global Environmental Engineers, 2018)
With the development and utilization of coal resources, the surface vegetation is destroyed and soil erosion is more and more serious. Open-pit coal mine on typical steppe causes very strong artificial erosion landform remodeling, especially mining dump slope, needing to take reasonable measures for its vegetation restoration. Irrigation is one of main means to ensure the vegetation growth on anthropogenic landforms, which can make up for a lack of atmospheric precipitation and coordinated uneven distribution of water space and enhance its competitiveness. The research focuses on different irrigation methods in the vegetation restoration of coal mine dump slope, which is slight spraying, drip irrigation and micro irrigation, where water shortages, lack of regular power and slope topography. Suitable irrigation methods are determined better to vegetation restoration and reconstruction through studying the characteristics of three irrigation methods, soil moisture content, vegetation coverage and biomass on the ground. Appropriate way of irrigation not only make more rational use of limited water resources, but also promote plant growth and protect coal mine slope, effectively reduce soil erosion.